A case of a rare autoimmune disease: Vogt-Koyanagi-Harada disease - Diabri, Banyama Marie; Bayala, Yannick Laurent Tchenadoyo; Bonkoungou, Marcellin; Traoré, Awa; Zabsonre/Tiendrebeogo, Joelle Wenlassida Stephanie; Ouedraogo, Dieu-Donné (Brazilian Journal of Case Reports, 2024)
Vogt-Koyanagi-Harada (VKH) disease is a rare autoimmune disorder. It is exceptional in black sub-Saharan Africans. A 27-year-old dermatology patient with progressive segmental vitiligo associated with bilateral visual acuity loss, headache, and hearing loss. Hypocromic macules were noted extending to the inner surface of the upper lip and to the right jugal region. Examination of the skin revealed poliosis of the moustache and scalp. Slit-lamp inspection revealed numerous corneal keratic precipitates. Optical coherence tomography (OCT) revealed chorioretinitis scarring in the right eye and macular and papillary atrophy in the left. Tone luminance audiometry revealed a 1st degree major hearing loss of the bilateral mixed type. We made the diagnosis of VKH syndrome. The patient received a bolus of methylprednisolone followed by prednisone. VKH disease is not common in sub-Saharan Africa. It is essential to consider this disease in all cases of segmental vitiligo.